OsNUDX23 regulates early seed germination by modulating ROS balance and starch metabolism in rice - Xing Dai; Xing Dai; Wenwen Kong; Feiyan Wu; Zijie Pan; Lei Gao; Beixin Mo; Yu Yu; Weigui Luo (Frontiers in Plant Science)
Seed germination is a complex biological process that encompasses the mobilization of stored nutrients, the resumption of metabolic activities, and the responses to various environmental stimuli. Reactive Oxygen Species (ROS) play a dual role during seed germination: at low concentrations, they function as signaling molecules to facilitate germination, while at high levels, they can induce oxidative damages. Therefore, maintaining ROS homeostasis through scavenging mechanisms is crucial for optimal seed germination. In this study, we investigated the role of OsNUDX23 in rice seed germination. Our findings indicated that OsNUDX23 acts as an active Nudix hydrolase towards diverse substrates including NAD, NADH, NADPH, FAD, and ADPG. Loss-of-function OsNUDX23 mutants displayed earlier coleoptile elongation, delayed radicle elongation and reduced germination rate during post-imbibition stages when compared to wildtype plants, suggesting its intricate role during seed germination. Transcriptome analyses revealed that OsNUDX23 influences the expression of genes involved in ROS metabolism and starch metabolism pathways. Further investigation revealed that OsNUDX23 inhibits the activity of NADPH oxidase (NOX) and reduces the accumulation of NADP+, resulting in elevated ROS levels in Osnudx23 mutants. Down-regulation of genes involved in starch and sucrose metabolism was observed in Osnudx23 mutants during post-imbibition, accompanied with accumulated starch content. Collectively, these results demonstrate that OsNUDX23 plays a critical role in rice seed germination by scavenging ROS to maintain redox balance and modulating starch metabolism.